Pengaruh Model Tokoh dalam Al-Qur’an Terhadap Kisah Inspiratif Islami “Yusuf Zulaikha: The Greatest Love Story”: Analisis Sastra Bandingan - Ahmad Sirfi Fatoni (Lembaga Penelitian dan Pengabdian Masyarakat Institut Agama Islam Nurul Hakim, 2024)
The character model was one of the studies in the comparative literature. One of the character models was the character model taken from the religious figure model. This study was a comparative literary study that had a different language and had an impression of influence between one work and another. This study used a comparative analysis of similarities using descriptive methods. This article examines the influence of the model of religious figures from the Arabic text of the Qur’an to non-Arabic literary works, the Islamic Inspirational Story